Comparative evaluation of six phenotypic methods for detecting extended-spectrum beta-lactamase-producing Enterobacteriaceae - Singh, Rajkumar Manojkumar; Singh, Huidrom Lokhendro (The Journal of Infection in Developing Countries, 2014)
Introduction: Various conventional phenotypic methods and automated systems have been evaluated for extended-spectrum beta-lactamase (ESBL) detection. There is a paucity of data comparing these methods using the same clinical isolates in eastern and north-eastern parts of India. The present study was designed to compare the capacity of six phenotypic methods to detect ESBLs in clinical isolates of Enterobacteriaceae. Methodology: A total of 206 non-duplicate clinical isolates of Enterobacteriaceae, obtained over a period of six months (July to December, 2012), were tested by the Vitek 2, double disk synergy tests (30 mm, 20 mm, and modified method), combined disk test, and ESBL Etest to evaluate their ability to detect ESBLs. Minimal inhibitory concentration (MIC) by the agar dilution method was used as the reference method. Result: The reference method detected ESBLs in 57 (27.7%) isolates. Among the six methods, the combined disk test demonstrated an overall agreement of 100% with the MIC. The Vitek 2 showed a sensitivity and specificity of 91.8% and 97.24%, respectively, with a positive predictive value of 93.33%. The sensitivities of the conventional methods ranged from 83% to 94%. The highest sensitivity and specificity were shown by combined disk (93.44%) and double disk synergy (100%) techniques, respectively. Conclusion: In our setting, Vitek 2 showed an acceptable capacity to detect ESBL isolates as it improved the turnover time (6 to 8 hours) in comparison to conventional phenotypic methods, which took a minimum of 24 hours. However, the combined disk test achieved the highest sensitivity.